Key Success Factors and Administrative Factors Affecting the Health Literate Organization Development for Sub-District Health Promoting Hospitals - Kuppatipattamakul, Nattachai; Prasit, Nakarin; Thummawongsa, Pittaya (Health Science Journal of Thailand, 2024)
This cross-sectional descriptive research aimed to study key success factors and administrative factors affecting the development of health-literate organizations for sub-district health-promoting hospital directors in Nakhon Phanom province. The study was based on a population of 152 directors; the sample size was 131 using simple random sampling. The reliability coefficient was found to be 0.99. Data was collected between 18 January and 16 February 2024. The statistics used to analyze the data were descriptive statistics and inferential statistics, including Pearson correlation coefficient and stepwise multiple linear regression. The significance level was set at 0.05. The results showed that overall key success factors and administrative factors had a high relationship with the health literate organization development for sub-district health promoting hospital directors in Nakhon Phanom province, (r = 0.844, p-value <0.001) (r = 0.832, p-value < 0.001), and the five variables include key success factors: image development of healthcare facilities, collaborations between sub-district health promoting hospitals and node hospitals, executives at all levels providing support, and follow-up to create understanding, administrative factors, technology, and management could jointly predict the health literate organizations development for sub-district health promoting hospitals directors at 80.0 percent (R2adj.=0.800).